Periodontal Treatment Reduces Matrix Metalloproteinase Levels in Localized Aggressive Periodontitis. Issue 12 (1st December 2013) - Gonçalves, Patricia Furtado; Huang, Hong; McAninley, Suzanna; Alfant, Barnett; Harrison, Peter; Aukhil, Ikramuddin; Walker, Clay; Shaddox, Luciana Macchion
Abstract : Background: Matrix metalloproteinases (MMPs) are a family of host‐derived proteinases reported to mediate multiple functions associated with periodontal breakdown and inflammation. High MMP levels in African‐American children with localized aggressive periodontitis (LAgP) have been reported previously by the present authors. However, little is known about MMP reductions in gingival crevicular fluid (GCF) after therapy. This study aims to evaluate MMP levels in the GCF after treatment of LAgP and to correlate these levels with clinical response. Methods: GCF samples were collected from 29 African‐American individuals diagnosed with LAgP. GCF was collected from one diseased site (probing depth [PD] >4 mm, bleeding on probing [BOP], and clinical attachment level ≥2 mm) and one healthy site (PD ≤3 mm, no BOP) from each individual at baseline and 3 and 6 months after periodontal treatment, which consisted of full‐mouth scaling and root planing (SRP) and systemic antibiotics. The volume of GCF was controlled using a calibrated gingival fluid meter, and levels of MMP‐1, MMP‐2, MMP‐3, MMP‐8, MMP‐9, MMP‐12, and MMP‐13 were assessed using fluorometric kits. Results: MMP‐1, MMP‐8, MMP‐9, MMP‐12, and MMP‐13 levels were reduced significantly up to 6 months, comparable to healthy sites at the same point. Significant correlations were noted between MMP‐2, MMP‐3, MMP‐8, MMP‐9, MMP‐12, and MMP‐13 levels and percentage of sites with PD >4 mm. MMP‐3, MMP‐12, and MMP‐13 levels also correlated with mean PD of affected sites. Conclusion: Treatment of LAgP with SRP and systemic antibiotics was effective in reducing local levels of specific MMPs in African‐American individuals, which correlated positively with some clinical parameters.